Teaching and Learning Cycle Technique Implication to Boost the Third Semester Students’ Ability in Grammar of D3 English Program of Universitas Bengkulu - Kasmaini Kasmaini (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
The aim of this research was to investigate the ability of the third semester students of D3 study program of universitas Bengkulu in using appropriate grammar by implementing the teaching and learning cycle technique. This is a classroom action research. It was done in genre writing class. There were 23 students. Three instruments were applied in this research such as observation, fieldnote and test. From the observation result, it could be seen that there was the students’ activeness and the increasing ability of the students in using grammar for certain text type. The fieldnote results also showed that the amount of the students asking in the class increased, the ability to make appropriate title for certain text type, the use of appropriate vocabulary and grammar increased too. From the last intrument, test, also found that there was significant increase of students’ average score from the first to the third cycle. The score was 64,71 and 82. At last, it can be concluded that the technique of teaching and learning is successful to increase students’ ability in using appropriate grammar for a certain text type.